Memórias para educação do munícipe: histórias do Portão do Ocoí por entre memórias escritas e memórias vividas - Parizotto, Rosangela (2017)
In the realization this research, I basically use two sources types: oral and written, that is, bibliographic research and field research, treated here as semi-structured interview. The intention is document these memories of the characters who helped in the formation (colonization) of the Portão do Ocoí District – Missal/PR, that even in the middle of the land tenure conflicts, caused the construction of the Church/School, which marks the creation and subsequent transition as Public institution, exploring the senses of space in four verbs: occupy, name, live and work. As it deals with research on memory history of local education, it was considered what already exists that is the didactic book, used as official source of the memory of the origin and plots of local education. Next to this official source, were recorded memories by oral history. We sought to understand and bring to writing the density of these memories and their conflicts at the same time demonstrate how they are articulated with the history education in Missal City and what the relationship of the school in the process of territorial occupation in the Portão do Ocoí, Territory of the municipality of Missal/ Paraná. I chose to research from the formation of the District in 1961 until 2017, since there are still many living inhabitants who helped in the formation of these communities and who are still part of it, thus helping to insert significant and new elements in the formation history of our municipality, in this case in the history of education